Aryl radical-induced desulfonylative ipso-substitution of diaryliodonium salts: an efficient route to sterically hindered biarylamines. Issue 42 (22nd April 2020) - Chen, Huangguan; Wang, Limin; Han, Jianwei
Abstract : By using vicinal aryl sulfonamide-substituted diaryliodonium salts, a cascade of desulfonylation/aryl migration was promoted by triethylamine in synthesis of sterically hindered biarylamines, which operated via a radical-induced reaction pathway. Abstract : By using vicinal aryl sulfonamide substituted diaryliodonium salts, a cascade of desulfonylation/aryl migration was promoted by triethylamine in the synthesis of sterically hindered biarylamines, which operated via a radical-induced reaction pathway. The products were readily converted into a variety of important synthons. Furthermore, coupling reactions of N -methyl biarylamine and 1, 6-dibromopyrene provided a potentially attractive molecule in OLEDs.